2013
DOI: 10.1117/12.2035986
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high precision metallic freeform mirrors with magnetorheological finishing (MRF)

Abstract: The fabrication of complex shaped metal mirrors for optical imaging is a classical application area of diamond machining techniques. Aspherical and freeform shaped optical components up to several 100 mm in diameter can be manufactured with high precision in an acceptable amount of time. However, applications are naturally limited to the infrared spectral region due to scatter losses for shorter wavelengths as a result of the remaining periodic diamond turning structure. Achieving diffraction limited performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Applying computer-aided polishing with sub-aperture tools, a roughness lower than 1 nm RMS is achievable [2]. Furthermore, local figuring techniques like Magnetorheological Finishing (MRF) enable the deterministic figure correction of NiP-layered metal surfaces [16].…”
Section: Electroless Nipmentioning
confidence: 99%
“…Applying computer-aided polishing with sub-aperture tools, a roughness lower than 1 nm RMS is achievable [2]. Furthermore, local figuring techniques like Magnetorheological Finishing (MRF) enable the deterministic figure correction of NiP-layered metal surfaces [16].…”
Section: Electroless Nipmentioning
confidence: 99%
“…In a next step the optical surface is processed by Magnetorheological Finishing (MRF), which is capable of performing local shape corrections with high accuracy [33]. The mechanism of local shape correction on electroless nickel plated metal mirrors as well as further process details can be found in [34].…”
Section: Finishing Operationsmentioning
confidence: 99%
“…Currently, as stated by Rhorer and Evans (2010), high-precision diamond turning is one of the processes used to generate high-quality optical surfaces. However, Beier et al (2013) found that diamond turning induces erratic jagged features. These imperfections could have an adverse effect on the performance of optical glasses, such as light scattering (Beier et al, 2013;Rubin, 2002;Trost et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…However, Beier et al (2013) found that diamond turning induces erratic jagged features. These imperfections could have an adverse effect on the performance of optical glasses, such as light scattering (Beier et al, 2013;Rubin, 2002;Trost et al, 2013). Rogov et al (2001) demonstrated that poor surface roughness adversely affected the light scattering factor.…”
Section: Introductionmentioning
confidence: 96%